"This Video Call May Be Monitored and Recorded": Video Visitation as a Form of Surveillance Technology and Its Effect on Incarcerated Motherhood. Issue 2 (1st December 2019) - JWells,
Abstract : This article argues that the implementation of video visitation in correctional facilities is a mechanism of control used to enact punitive measures for regulating mothers who act outside the dominant paradigms of motherhood. Because prisons were designed to surveil and mothers have historically been surveilled by institutions, incarcerated mothers are often overlooked when we discuss the surveillance methods used to keep institutionalized motherhood intact. This article builds on existing scholarship characterizing surveillance technology's role in criminalizing poor mothers of color, and considers the ways in which surveillance technology is used to normalize these mothers during their incarceration. Applying a Foucauldian framework, this article explores how adapting Video Visitation (VV)—a Skype-like video chat program—enables correctional facilities to extend the role of "watcher" and expand the panoptic gaze, which prompts mother-to-mother surveillance and intensifies self-surveillance. The article concludes by drawing attention to VV's structure and its ability to expand correctional facilities' surveillance to the children of incarcerated mothers.